From social movement to political power. An approach to feminist parties: the case of the French Unified Feminist Party and the Spanish Feminist Party - Jareño Gila, Claudia (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2024)
The purpose of this article is two-fold. On the one hand, it proposes to study the origins of the French Unified Feminist Party and the Spanish Feminist Party, whose history is part of the second feminist wave, a moment of massive irruption of women into the public sphere. This text thus sets out to study the contributions and debates that arose at the time of their creation, such as the question of women taking power and the links between the two organisations, which bear witness to the importance of personal contacts and international networks in the formation and development of feminist movement. On the other hand, it aims at analysing the current debates on these organisations in a context where feminist movements are particularly dynamic and right-wing extremism is on the rise in both France and Spain. By combining a diachronic and synchronic perspective on the debates emerging from these organisations, it is possible to create a dialogue between past and present on some of the issues that the feminist movement has encountered from the last third of the 20th century to the present day, such as women’s political participation or what feminism is about. This approach not only makes it possible to trace and uncover the history of feminist parties, but also to entrench the current feminist debates about these parties into the collective historical memory of the feminist movement.